2014
DOI: 10.3390/antiox3030516
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Antioxidative Properties of Borneo Indigenous Liposu (Baccaurea lanceolata) and Tampoi (Baccaurea macrocarpa) Fruits

Abstract: Two underutilized indigenous fruits of Borneo, Liposu (Baccaurea lanceolata) and Tampoi (Baccaurea macrocarpa) were investigated for their total phenolic (TPC), flavonoid (TFC), anthocyanin (TAC) and carotenoid (TCC) contents as well as antioxidant properties in vitro. The fruits were separated into three different parts (i.e., pericarp, flesh and seed) and extracted using 80% methanol. Antioxidant activity was determined using DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging, ABTS decolorization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…B. lanceolata and B. macrocarpa . It was reported that the fruits of B. macrocarpa exhibited the highest antioxidant activity compared with B. lanceolata , which significantly correlated with the phenolic and flavonoid contents 7 .…”
Section: Introductionmentioning
confidence: 94%
“…B. lanceolata and B. macrocarpa . It was reported that the fruits of B. macrocarpa exhibited the highest antioxidant activity compared with B. lanceolata , which significantly correlated with the phenolic and flavonoid contents 7 .…”
Section: Introductionmentioning
confidence: 94%
“…B. lanceolata and B. macrocarpa. It was reported that the fruits of B. macrocarpa exhibited the highest antioxidant activity compared with B. lanceolata, which significantly correlated with the phenolic and flavonoid contents 5 .…”
Section: Introductionmentioning
confidence: 94%
“…The ability of the extracts to reduce Fe 3+ to Fe 2+ was determined using the Ferric Reducing Power Antioxidant (FRAP) assay by method of Benzie 37 as modified. 38 A working FRAP reagent was prepared by mixing 20 mL of 4 2,4,6-Tripyridyl-S-Triazine, 200 mL acetate buffer, 20 mL ferric chloride and 24 mL distilled water in a 10:1:1 ratio. The mixture was heated to 37°C in a water bath.…”
Section: The Ferric Reducing Antioxidant Power Assay (Frap)mentioning
confidence: 99%